An association study of interleukin-4 gene and preeclampsia in Taiwan - Lin Kang; Chung-Hwan Chen; Chen-Hsiang Yu; Chiung-Hsin Chang; Fong-Ming Chang (Elsevier, 2014)
Objective: To test whether the interleukin-4 (IL-4) gene polymorphisms could be used as markers of susceptibility for preeclampsia in Taiwan. Materials and methods: This study included 78 women with preeclampsia and 125 normal controls. A polymerase chain reaction was used to analyze the variable number of tandem repeats polymorphism for the IL-4 gene intron 3. Restriction fragment length polymorphism analysis using endonuclease BsmFI was performed for the IL-4 gene at the promoter −590 position. The association between the genotype and disease was examined using Chi-square tests. Results: We found no significant differences in the genotype distributions and allele frequencies for the IL-4 gene at both promoter and intron 3 regions between the preeclampsia and control groups. Conclusion: Even though this is the first study investigating the association between the promoter region and intron 3 polymorphisms of IL-4 and preeclampsia worldwide, our data do not support a role of the IL-4 gene in the pathogenesis of preeclampsia in Taiwanese women.